The Influence of the Number of Threads on the Archimedes Screw Turbine Prototype for Green and Renewable Energy Generation - Eva Kurnia Yulyawan; Indro Wicaksono; Indah Noor Dwi Kusuma Dewi; Ahlan; Wahyu Nur Achmadin (ENERGY: JURNAL ILMIAH ILMU-ILMU TEKNIK, 2022)
Energy  needs  in  Indonesia  are  currently  still  dominated  by  energy  based  on  fossil  fuels,  such  as  oil  and  coal. The  disadvantage  of  fossil  fuels  is  that  they  are  not  environmentally  friendly.  Water  is  an  alternative  energy source that can replace fossil-based energy sources and is a renewable energy. The Archimedes Screw turbine is a  turbine  suitable  for  use  in  Indonesia  which  has  a  low head  river  flow.This  research  uses  an  experimental method, namely designing and manufacturing an Archimedes Screw turbine. The results of the 180 minute test of the three Archimedes screw turbine models, namely threads screw type 1 produces a voltage of 2.83 volts, screw type 2 produces a voltage of 3.16 volts and screw type 3 produces a voltage of 2.49 volts. Thread type 2 which can produce a greater voltage for 180 minutes, which is 3.16 volts.